Temporal and concentration effects of isoflurane anaesthesia on intestinal tissue oxygenation and perfusion in horses. Issue 1 (July 2015) - Hopster, K.; Hopster-Iversen, C.; Geburek, F.; Rohn, K.; Kästner, S.B.R.
Highlights Depth but no duration of isoflurane anaesthesia influences global and gastrointestinal perfusion and oxygenation. There is linear correlation between isoflurane concentration and central perfusion. There is non-linear correlation between isoflurane concentration and gastrointestinal perfusion. Gastrointestinal perfusion seems to be preserved until MAP threshold of about 60 mmHg or CI of 50 mL/kg/min.